The Gut Microbiota and Its Connection to Neurological Disorders - summary of current knowledge - Sysło, Oliwia; Jung, Magdalena; Jung, Maximilian; Sławińska, Barbara; Jaworski , Aleksander; Goliat, Weronika; Haraziński, Konrad; Rzepka, Maciej; Nalepa, Magdalena; Gutowski, Piotr (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: The gut microbiota plays a crucial role not only in absorption, metabolic, and immune processes but also increasingly in shaping behavior and is strongly linked to the gut-brain axis. Different sections of the digestive system, due to varying environmental conditions and physiological functions, have a unique microbiota composition, both quantitatively and qualitatively, including bacteria, fungi, and archaea. This study aims to review current scientific research on the impact of the gut microbiome on the gut-brain axis and to explore how this influence may affect neurological disorders. Brief Description of the State of Knowledge: Dysbiosis in the digestive system leads to changes in the composition of the gut microbiome, which can significantly impact the development and progression of various mental health conditions, as indicated by numerous clinical studies examining the gut-brain axis correlation. The main challenge is the insufficient understanding of which microorganisms within the human microbiota have positive or negative effects on mental health. Therefore, further research is needed to better elucidate these mechanisms. Summary: Neurological disorders are a common challenge in clinical practice. Evaluating gut microbiota and metabolic states may provide valuable diagnostic and therapeutic insights, potentially improving patients’ quality of life. Materials and Evidence: A literature review was conducted using the PubMed database.